Behind the screens: connecting experiences and technology, in the pandemic, about teaching Mathematics in the Elementary School - França, Simone de Miranda Oliveira; Leite, Vânia Finholdt Angelo (Educação Matemática Debate, 2023)
This work aims to understand the place that knowledge, produced by experience, occupies in the teaching of Mathematics in the Elementary School, from the Covid-19 pandemic. It takes as a reference the approaches that deal with the pandemic impacts to teach Mathematics in this school stage, in the light of the knowledge of experience and the use of different technological resources. It is based on the theoretical-methodological approach of the narrative present in the dialogues with the participating teachers. The study showed, among other elements, that approaches such as debates, drawings, games and manipulation of manipulable objects were predominant for learning mathematics in a remote context. It also indicated that the appropriation of technological resources by the teachers, especially the digital ones, highlighting a process of digital literacy, occurred individually, as a form of self-training, with their experiences in the classroom predominating.